Effects of substrates on the performance of optoelectronic devices: A review. Issue 1 (1st January 2020) - Asare, Joseph; Agyei-Tuffour, Benjamin; Amonoo, Evangeline A.; Dodoo-Arhin, David; Nyankson, Emmanuel; Mensah, Bismark; Oyewole, Oluwaseun O.; Yaya, Abu; Onwona-Agyeman, Boateng
Abstract: This review discusses the effects of substrates on devices fabricated for optoelectronic applications. It includes the types and characteristics of substrates, synthesis and fabrication of substrates, and the influence of substrates on the optical properties, surface morphology and current-voltage behaviour of optoelectronic devices. The study showed that two main types of substrates: planar and textured are commonly used in the industry. Flexibility, semi-rigidity and rigidity are characteristics of the substrates and they vary in modulus, transparency and texture. Whereas glass and metal substrates can be produced via melt casting, polydimethylsiloxane (PDMS), polyethylene terephthalate (PET), etc are produced by crosslinking polymer base materials with curing agents. The mechanical and current-voltage characteristics are also shown for planar and textured substrate-based devices. The textured substrates showed ridges, wrinkles, buckled surface morphology whereas the planar showed uniform and largely flat morphology. Textured substrates also recorded higher optical absorbance and improved device efficiencies compared with planar substrates. The molecular configuration of the polymer chains are edged-on for planar substrates and both edge-on and face-on for textured substrates. The findings and their implications have been discussed to highlight the importance of substrates in the fabrication and performance of optoelectronic devices.